Quantifying Interannual Variations in Groundwater Fluxes Within a Braidplain Aquifer Using Active‐Distributed Temperature Sensing - A. J. Sai Louie; L. K. Morgan; D. Dempsey; S. Wilson; E. W. Banks (Water Resources Research, 2025)
Abstract Braided rivers are a significant contributor to groundwater flow in braidplain aquifer (BPA) systems, yet the spatiotemporal variations in flow exchange remain poorly understood. This study presents an extensive active‐distributed temperature sensing data set collected over a 3‐year period from two 100‐m long fiber optic cables installed up to ∼5 m depth below a braided river channel in New Zealand to quantify specific discharge (i.e., parafluvial flow) within the BPA at high spatial resolution. Despite river flow fluctuating by two orders of magnitude, specific discharge within the BPA showed moderate variation, with values ranging from 3.5 to 5.9 m d−1 on HDD1 (20.4% variance relative to the median) and from 2.4 to 4.5 m d−1 on HDD2 (13.3% variance relative to the median) over the study period. Geomorphology influences hydraulic conductivity, thereby affecting the hydraulic gradient. Following a flood event, specific discharge increased beneath the river margins over time, with the largest increase corresponding with areas of greatest geomorphic change, and changes to the subsurface flow dynamics. Surveys conducted after the flood event, where river flow peaked at 225 m3 s−1 (compared to a median of 2.51 m3 s−1), showed a marked increase in specific discharge. These subsurface changes occurred gradually, with no obvious seasonal influence, compared to rapid geomorphic surface alterations. This translates to variable specific discharge within the BPA in both space and time caused by changing bedform and connectivity to preferential flowpaths. Geomorphic changes following a flood event had the largest impact on specific discharge.